Augmented Reality Application for Sink Location Information in Niti Mandala Renon Field - Awan, Diky Rizky; Muliantara, Agus (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2021)
Currently, the whole world is experiencing a pandemic outbreak of the COVID-19 virus, which is an infectious disease that is one of the types of coronavirus. Transmission of this virus can go through the surrounding goods that are touched by the hand so it is recommended to always maintain hand hygiene by washing hands with water and soap. Not at every entrance in Niti Mandala Renon field, there is a sink and no information about the location of the sink in this field, which can cause the community to be confused due to lack of information. Augmented Reality (AR) applications can be used to solve this problem because with AR can explain more interactive information because the information displayed through 3D objects is directly applied to the real world visually. In this case, AR is used to display the map of sink location information with an interactive 3D model that can be rotated and zoomed to help the community easily get the information. This application use marker-based AR with multi-target so that each map information is stored and display on the different marker. Users only need to install the application on their android device and scan the QR code provided, then the 3D map object will be displayed according to the registered marker. Based on testing this study gets a 100% success rate in functional aspects.